Isolation and Characterization of H1 Subtype Swine Influenza Viruses Recently Circulating in China - Minghao Yan; Tianxin Ma; Xiaona Shi; Qin Chen; Luzhao Li; Bangfeng Xu; Xue Pan; Qiaoyang Teng; Chunxiu Yuan; Dawei Yan; Zhifei Zhang; Qinfang Liu; et al. (Viruses)
Pigs serve as a mixing vessel for influenza viruses and can independently promote the emergence of pandemic strains in humans. During our surveillance of pig populations from 2021 to 2023 in China, 11 H1 subtype swine influenza viruses (SIVs) were isolated. All viruses were reassortants, possessing internal genes of identical origins (PB2, PB1, PA, NP, M: pdm09/H1N1 origin, NS: North American triple reassortant origin). The H1N1 isolates were all the dominant G4 EA H1N1 viruses in China. Two H1N2 isolates carried early human pdm09/H1N1 HA genes, suggesting a possible pig-to-human transmission route. Mutations that dictate host range specificity were identified in all isolates, a phenomenon which may enhance the affinity to human receptors. These H1 subtype viruses effectively replicated both in vivo and in vitro without prior adaptation and exhibited different pathogenicity and growth characteristics. Some of the H1 viruses were even found to cause lethal infections in mice. Taken together, our study indicates that the H1 subtype SIVs recently circulating in China pose a potential threat to human health and emphasizes the importance of continuing to closely monitor their evolution and spread.